Double step paraneoplastic brainstem encephalitis: a clinicopathological study. Issue 6 (15th May 2009) - Vigliani, M-C; Novero, D; Cerrato, P; Daniele, D; Crasto, S; Berardino, M; Mutani, R
Abstract : A case of brainstem encephalitis in a man positive for both anti-Hu and anti-Ri antibodies is reported. This case had an unusual double step evolution and progressive involvement of different CNS subdivisions at MRI. Brainstem encephalitis developed abruptly, mimicking a posterior vascular deficit with vertigo and dizziness. These symptoms transiently remitted completely after a few days to relapse acutely 1 month later with sudden loss of consciousness, followed by confusion, disorientation, dysarthria, dysphagia and reduced thermic sensation on the right side. Within another few days, the patient developed acute respiratory failure and died some weeks later. MRI was negative at the beginning but later showed a progressive ascending involvement of the brainstem and thalamus. At autopsy, this picture corresponded to lymphocytic infiltration, preferentially B cells into the perivascular spaces and T cells in the brainstem parenchyma, confirming that T cells could be the effector of cytotoxicity, probably in the presence of cooperation with B cells that were well represented in this setting.